RENCANA PENGEMBANGAN SDIT AZ-ZAHRA STABAT - Sulaiman Rasid (Journal of Community Devation, 2025)
Schools as educational institutions must be able to respond to the demands of the times and be able to demonstrate their existence as controllers of change. Schools must continue to develop their institutions with strategies and management that are able to effectively produce quality educational output. Then the school must also have a new vision and mission, and be equipped with adequate facilities, management and more trained teaching staff so that it can improve the school's status as a model school and become an example of educational development standards. all other schools in Indonesia